Gejala Perubahan Penguasaan Kebun Plasma dan Berkembangnya Ketidakmerataan Pendapatan pada Komunitas Petani PIR-BUN - Undang Fadjar; Bambang Dradjat; Melani A. Sunito (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2002)
EnglishOne of the programs for the village development that fulfill the goal for the growth and equality distribution of income is the partnership program for the Perusahaan Inti Rakyat Perkebunan (PIR-BUN). The objective of this program, beside to increase the productivity and the efficiency of public plantation effort is also to grant the opportunity for managing a business for the poverty stratum that do not possess plantation and fund but have the human resources capability. Then, all participants of the program are given a plasma plantation with the same width. Therefore, in support of the PIR-BUN program, the plasma plantation is the bridging for a farmer to attain the chance to increase their financial income. This research is done as a study case toward the four locations of PURBUN rubber plants that was chosen by purposive sampling. The four locations are consist of Rimbo Bujang (RB), Jambi, (Talang Jaya) Sumatera Selatan, Monterado-Kinande (MD) Kalimantan Barat, and Danau Salak (DS), Kalimantan Selatan. Data and the information was gathered and analyzed using quantitative analysis (t-test), Gini index, and descriptive statistic). The result of this research shows that in all locations there has been a change of authorized foundation of the plasma plantation, which causes not only the permanent ownership of the foundation but also the temporary ownership of the foundation. Beside that, the changes of the ownership, the width of the foundation, and the changes of the position of the ownership from being the